Team Tidyboy at the WRS 2020: a modular software framework for home service robots. (17th September 2022) - Kang, Taewoong; Song, Dongwoon; Yi, Jae-Bong; Kim, Joonyoung; Lee, Chung-Yeon; Yoo, Youngjae; Kim, Minji; Jo, Hyun-Jun; Zhang, Byoung-Tak; Song, Jaebok; Yi, Seung-Joon
Abstract : This paper describes Team Tidyboy's approach to build a functional, robust, yet highly modular software framework for home service robots. Home service tasks require a number of software modules to work together, which includes verbal and nonverbal human robot interactions, 3D perception of known and unknown objects and manipulation of various objects using movement of both the manipulator and the base of the robot. World Robot Summit (WRS) 2020 Partner Robot Challenge (PRC) rule has raised the bar higher by asking for a reliable, long-term operation of such a system without human intervention. We present how we have overcome such challenges by robust software modules, repeated experiments in randomly initialized simulated environments, and finally introduction of various failure detection and recovery algorithms. Our software is successfully validated in RoboCup@Home 2021 and WRS 2020 PRC remote participation league, which led us to obtaining the first places in both competitions. GRAPHICAL ABSTRACT: UF0001